Enhancing Primary Pupils' Geometric Thinking Through Phase-Based Instruction Using The Geometer's Sketchpad - Chew , Cheng Meng; Lim , Chap Sam (Penerbit Universiti Sains Malaysia, 2013)
The purpose of this study was to enhance primary pupils' geometric thinking through phase-based instruction using The Geometer's Sketchpad (GSP) based on the van Hiele theory of geometric thinking. Specifically, it sought to examine Year Four pupils' van Hiele levels of geometric thinking about equilateral triangle, square, regular pentagon and regular hexagon before and after phase-based instruction using GSP, and whether there was any significant difference in the pupils' van Hiele levels of geometric thinking about the regular polygons after the intervention. The researchers employed an exploratory case study research design and purposeful sampling to select a class of 26 mixed-ability Year Four pupils from a primary school in Selangor. A van Hiele level test based on Mayberry's (1981) test and scoring criteria was devised and administered to the pupils before and after the intervention to assess their van Hiele levels of geometric thinking about the regular polygons. The results of the pre-test showed that the pupils' initial van Hiele levels were predominantly at Level 0 (Pre-recognition) for regular pentagon and regular hexagon but at Level 1 (Recognition) for equilateral triangle and square. However, the results of the post-test revealed that the pupils' van Hiele levels after the intervention were predominantly at Level 2 (Analysis) for all the regular polygons. In addition, the results of the Wilcoxon test showed that there was a significant difference in the pupils' van Hiele levels of geometric thinking for all the regular polygons after phasebased instruction using GSP. The median van Hiele level in the post-test was higher than the median van Hiele level in the pre-test for all the regular polygons, indicating that the intervention had significantly enhanced the pupils' geometric thinking about the regular polygons.